Otih ka Kaleh Wabla: The intentionality of consciousness within multi-functional spatial configurations in Makaling (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Makaling Village, located in South Papua Province, exhibits multi-functional spatial characteristics that operate on two scales: micro and meso. The village is inhabited by the Coastal Malind, a sub-tribe of the Malind Anim, whose spatial practices generate distinctive multi-functional spatial phenomena. In contemporary urban contexts, the concept of multifunctionality and the pursuit of modernity often require flexible spatial arrangements to accommodate diverse activities within a single space. This tendency is largely driven by the limitations of land availability amid increasing population pressure and escalating spatial demands. In contrast, rural settlements such as Makaling reveal a different manifestation of multifunctionality known as kamem la sai, which embodies deeper spatial and cultural layers beyond what is physically perceptible. This phenomenon is rooted in a local philosophical concept referred to as otih ka kaleh wabla. The study employs eidetic reduction analysis within the framework of Husserl’s transcendental phenomenological qualitative research. Data were collected through in-depth interviews and direct field observations, leading to the identification of several observation units, thematic structures, and conceptual layers each corresponding to stages of phenomenological reduction. The primary objective of this research is to articulate the intentional awareness inherent in the kamem la sai phenomenon in Makaling, as revealed through the phenomenological reduction process. The implications of this study extend to the development of human resources in architectural academia, the formulation of government policies, spatial planning practices, and architectural design approaches in Merauke, Papua. Furthermore, the research contributes to the advancement of theoretical discourse on multi-functional space, local wisdom, and transcendental meaning within the context of Papuan vernacular settlements.
Keywords: Papuan society; Transcendental phenomenology; Vernacular settlements